Ngaji Rasa dalam Pandangan Komunitas Dayak Indramayu - Khaerul Umam (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
The belief system, in many different aspects, is not created from an empty space. It emerges from many different and extraordinary experiences of human life and has sacred dimension. In practice, however, this belief system needs a medium to be understood and implemented. This research explores the mystical aspect of the belief system among Dayak community in Indramayu by employing field research method. This study shows that Ngaji Rasa is the actualization of the belief system which emerges from the life history of Dayak community in Indramayu among their extraordinary experiences around their world. The doctrine of Ngaji Rasa emphasizes understanding spiritual dimension of the shelf before assessing and judging of others. In addition, include as one principle in Ngaji Rasa is to determine whether one self is ready or not to accept something from others in the relationships between human being and other creatures. The aphorism of “if being hit was hurt, so do not hit others,” is the principle of Ngaji Rasa in Dayak Indramayu.